Mental Health in Non-Oncologic Urology Patients - Danyon Anderson; Devesh Kumar; Divya Divya; Jose L. Zepeda; Abrahim N. Razzak; Jamal Hasoon; Omar Viswanath; Alan D. Kaye; Ivan Urits (Health Psychology Research)
This article is a literature review of mental health concerns in non-oncologic urology patients. Pathologies represented in this review include Peyronie's Disease (PD), erectile dysfunction (ED), urinary incontinence and urinary tract infections (UTI), infertility, benign prostatic hyperplasia (BPH), kidney stones, and urinary retention. While there has been great interventional focus as of late for urogenitary malignancies (i.e. prostate cancer awareness with the Movember campaign), literature studies and intervention focused on non-oncologic urology patients has been limited. As such, we conducted a review on urology patients with non-oncologic pathologies as an effort to increase clinician awareness of mental health concerns among such patients, increase the comfort level for clinician communication on socially sensitive topics surrounding pathologies, and review ongoing interventions conducted within these pathologies. We outlined different ongoing Mental Health Illness (MHI) needs and treatments for various pathologies. Patients with non-cancerous urologic pathologies had lower quality of life and higher incidence of MHI than the general population. As such, in line with the American Urological Association recommendations, psychological and social support from peers, therapists, and healthcare providers further prove to be crucial for some subpopulations. The review also yielded pathology specific interventions such as group therapy for ED patients. Given the higher incidence of MHI in the patient population after the Covid-19 pandemic, MHI awareness in the sphere of non-oncologic urology treatment continues to be crucial when creating a collaborative treatment platform for patients.